2004
DOI: 10.1093/nar/gkh277
|View full text |Cite
|
Sign up to set email alerts
|

The DNA-binding properties of the ARID-containing subunits of yeast and mammalian SWI/SNF complexes

Abstract: SWI/SNF complexes are ATP-dependent chromatin remodeling complexes that are highly conserved from yeast to human. From yeast to human the complexes contain a subunit with an ARID (A-T-rich interaction domain) DNA-binding domain. In yeast this subunit is SWI1 and in human there are two closely related alternative subunits, p270 and ARID1B. We describe here a comparison of the DNA-binding properties of the yeast and human SWI/SNF ARID-containing subunits. We have determined that SWI1 is an unusual member of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
81
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(84 citation statements)
references
References 36 publications
3
81
0
Order By: Relevance
“…ARID1B was found to bind to DNA without sequence specificity and is a component of BAF complexes containing either BRM or BRG1 (22,23). However, ARID1B and ARID1A are coincides with the results of previous studies.…”
Section: What Is Arid1b?supporting
confidence: 70%
See 1 more Smart Citation
“…ARID1B was found to bind to DNA without sequence specificity and is a component of BAF complexes containing either BRM or BRG1 (22,23). However, ARID1B and ARID1A are coincides with the results of previous studies.…”
Section: What Is Arid1b?supporting
confidence: 70%
“…ARID consists of approximately 100 amino acid residues and has been found to bind to DNA without sequence specificity (22,23). Missense mutations in this domain are likely to disrupt the DNA-binding ability of ARID1B and compromise the function of the BAF complex.…”
Section: Impact Of Arid1b Mutationsmentioning
confidence: 99%
“…The ARID domain in the Dead ringer protein has been shown to have DNAsequence specific binding; whereas ARID from OSA binds DNA with no sequence specificity [51,[55][56][57]. The ARID domain from yeast Swi1 is not a typical member of the ARID family, because it likely has weaker DNA binding affinity due to changes in key residues that normally interact with the major groove of DNA [58]. Swi3 has two known domains that have affinity for nucleosomes and DNA that are called SWIRM and SANT.…”
Section: Nucleosome Remodeling Complexes Swi/snf Familymentioning
confidence: 99%
“…Here we report the discovery of ARID1A as a candidate TSG in the T47D breast cancer cell line by using this approach. ARID1A encodes a human homolog of yeast SWI1, which contains a DNA-binding motif (AT-rich interactive domain, ARID) and is an integral member of the hSWI/SNF complex, an ATPdependent, chromatin-remodeling, multiple-subunit enzyme (Takeuchi et al, 1997(Takeuchi et al, , 1998Dallas et al, 1998Dallas et al, , 2000Wang et al, 2004;Wilsker et al, 2004;Patsialou et al, 2005). An increasing body of evidence has demonstrated that SWI/SNF complexes have important roles in gene regulation (Winston and Carlson, 1992;Carlson and Laurent, 1994;Hirschhorn et al, 1995;Kennison, 1995;Sudarsanam et al, 1999Sudarsanam et al, , 2000, cell proliferation (Nagl et al, 2005(Nagl et al, , 2006(Nagl et al, , 2007 and development (Carlson and Laurent, 1994;Kennison, 1995).…”
Section: Introductionmentioning
confidence: 99%